Human Identification Using Contrast Enhanced Segmented Palm-Vein Images. Issue 1 (December 2020) - Nandini, K; Surendran, T.; Sobana, S.; Chitra, B. K.; Kalaiselvi, T.
Abstract: This paper presents new approaches in biometrics is palm vein recognition system. By coding the alignment protective features by having a potential deformation, translational and rotational change. A palm vein authentication done by image analysis technique of vascular image of a person. Here we use four different algorithm to process the Near-Infrared Image of palm vein image. The algorithm are 1)juncture point algorithm 2)hand geometry algorithm 3) pose invariant algorithm 4) rank of the matrix. The output is kept in database as a each person as unique vascular pattern, the authentication is done by comparing Database pattern and plam vein pattern of a person to be authenticated.